The Malaysian’s Perception on Premium Print Advertisement - Lim, John Kheng Hock (2012)
This research is to examine the perception and purchase intentions of Malaysians on premium print advertisement as previous study that had been carried out on the topic was done in European countries. Utilizing the quantitative method, questionnaires was employed as the measuring instrument assisted by three perfume advertisements printed in premium print manner. A total of 229 samples were taken from the general public and the data collected showed that the premium-print advertisement were perceived as unique, prestigious, brand appealing and increased intentions to buy and pay a premium. Furthermore, results also confirmed previous studies regarding gender’s influence on new information processing. This study proves that a positive influence of premium print advertising may prove worthwhile for the industry in their rebranding and brand positioning exercise as consumers use their impressions of advertising cost as a cue to evaluate the advertised brand and, possibly, form resulting behavior (Kirmani, 1990).